Identifikasi Miskonsepsi Murid pada Materi Larutan Penyangga Menggunakan Five-Tier Diagnostic Test Kelas XI SMA - Tasya Zuhrah Ramadhani; Rasmiwetti Rasmiwetti; Abdullah Abdullah (MASALIQ, 2026)
Misconceptions about buffer solutions are an important issue in chemistry learning because they can affect students’ understanding of advanced concepts related to acid–base equilibrium. This study aims to identify students’ misconceptions about Grade XI buffer solution material at SMA Negeri 15 Pekanbaru. This study used a descriptive analytical method with a quantitative approach. The research sample consisted of 122 Grade XII students at SMA Negeri 15 Pekanbaru who had studied buffer solution material. Data were collected using a five-tier diagnostic test instrument consisting of 20 items as well as interviews using a purposive sampling technique. The results showed that students’ misconceptions about buffer solution material as a whole reached 26.71% and fell into the low category. Based on the concepts analyzed, misconceptions about the definition of buffer solutions reached 27.14%, the properties of buffer solutions 30.60%, the working principles of buffer solutions 16.39%, differences among buffer solutions 25.41%, pH calculations for buffer solutions 30.21%, the role of buffer solutions in the human body 25.00%, and methods of preparing buffer solutions 32.24%. The identified sources of misconceptions came from books at 12.581%, teachers 8.45%, personal reasoning 65.19%, peers 10.28%, and the internet 3.82%. The conclusion of this study affirms that students’ misconceptions about buffer solution material are still found in several concepts, especially in preparation methods, properties, and pH calculations of buffer solutions. These findings provide a practical contribution for chemistry teachers in designing more appropriate learning strategies and diagnostic evaluations to reduce misconceptions about buffer solution material.